Projeto de elementos de uma caixa de redução com um eixo de entrada e dois de saída para o protótipo do veículo da equipe Baja UFSCar - Bispo, Lucas Henrique da Silva (Universidade Federal de São Carlos, 2023)
Using a 4wd system in an off road vehicle is of utmost importance to overcome challenging terrain and overcome obstacles. Thus, the implementation of a 4x4 model in the Baja UFSCar team prototype can play an important role in the evolution of the project. However, the engine used in the Baja SAE Brasil competitions has a low power and knowing that the purpose of the project is to stimulate creativity and development of the students, the possible types of transmission that could adapt the vehicle to the 4x4 system were analyzed, so that the important factor for decision was the possibility of manufacturing by the students themselves. The present work aims to design the elements directly involved in the transmission of power from a fixed reduction box for the vehicle prototype of the Baja UFSCar team, so that it enables the transfer of power from the engines to the four wheels. Methodologies exposed in the books on the design of machine elements for shaft sizing, cylindrical and bevel gears will be used, because they are references enshrined in the subject. The design of the new gearbox was based on having minimum yield of 85%, a tolerance of ±0.6% for the actual reduction compared to the desired nominal, for both output axes and allow an assessment of the impact of the mass increase of the 4x2 system when moving to the 4x4 system.
Design of elements of a reduction box with one input shaft and two output for the prototype of the Baja UFSCar team vehicle
Keywords: Transmissão 4x4; Projeto mecânico; Caixa de redução; Eixos; Engrenagens cônicas; Engrenagens cilíndricas; 4x4 transmission; Mechanical design; Reduction box; Axes; Conical gears; Cylindrical gears; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS